Oral mucosa - an examination map for confocal laser endomicroscopy within the oral cavity: an experimental clinical study - Oetter, Nicolai; Pröll, Jonas; Sievert, Matti; Goncalves, Miguel; Rohde, Maximilian; Nobis, Christopher-Philipp; Knipfer, Christian; Aubreville, Marc; Pan, Zhaoya; Breininger, Katharina; Maier, Andreas; Kesting, Marco Rainer; et al. (Clinical Oral Investigations, 2024)
Objectives: Confocal laser endomicroscopy (CLE) is an optical method that enables microscopic visualization of oral mucosa. Previous studies have shown that it is possible to differentiate between physiological and malignant oral mucosa. However, differences in mucosal architecture were not taken into account. The objective was to map the different oral mucosal morphologies and to establish a “CLE map” of physiological mucosa as baseline for further application of this powerful technology. Materials and methods: The CLE database consisted of 27 patients. The following spots were examined: (1) upper lip (intraoral) (2) alveolar ridge (3) lateral tongue (4) floor of the mouth (5) hard palate (6) intercalary line. All sequences were examined by two CLE experts for morphological differences and video quality. Results: Analysis revealed clear differences in image quality and possibility of depicting tissue morphologies between the various localizations of oral mucosa: imaging of the alveolar ridge and hard palate showed visually most discriminative tissue morphology. Labial mucosa was also visualized well using CLE. Here, typical morphological features such as uniform cells with regular intercellular gaps and vessels could be clearly depicted. Image generation and evaluation was particularly difficult in the area of the buccal mucosa, the lateral tongue and the floor of the mouth. Conclusion: A physiological “CLE map” for the entire oral cavity could be created for the first time. Clinical relevance: This will make it possible to take into account the existing physiological morphological features when differentiating between normal mucosa and oral squamous cell carcinoma in future work.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Confocal laser endomicroscopy; Head and neck cancer; Optical methods; Oral carcinoma; Oral cavity; Oral cavity squamous cell carcinoma